Forest cover and social relations are more important than economic factors in driving hunting and bushmeat consumption in post-frontier Amazonia. (January 2021) - Carignano Torres, Patricia; Morsello, Carla; Parry, Luke; Pardini, Renata
Abstract: Identifying the economic drivers of hunting and bushmeat consumption is crucial for understanding whether economic growth in tropical forest regions can foster poverty alleviation and biodiversity conservation. However, studies investigating those drivers have drawn contrasting conclusions. Some authors attribute inconsistent findings to heterogeneous spatial and environmental contexts, yet other studies indicate that social factors may predominate over economical determinants. Here, we investigate bushmeat hunting and consumption by analyzing the relative importance of household-scale economic factors in diverse spatial and environmental contexts. We surveyed 240 households distributed across twenty diverse rural landscapes in a post-frontier region in Brazilian Amazonia. Our results show that hunting is more likely in locations with higher forest cover, where game availability is expected to be higher. In contrast, bushmeat consumption is widespread even in deforested landscapes near to urban centers. However, we find no evidence that household-scale economic factors determine variation in rural bushmeat consumption, regardless of spatial or environmental context. Consequently, we infer that future growth in income or wealth would be unlikely to significantly change patterns of bushmeat hunting and consumption. Instead, we find that eating bushmeat is mainly dependent on the hunting of relatively common species for subsistence and food sharing, rather than through market exchange. This demonstrates an important informal economy maintained by social relations. Work is needed to evaluate the sustainability of hunting these small to medium-sized species given they evidently provide useful ecosystem service to poor households and are likely to support social relations in rural Amazonia. Highlights: Understanding bushmeat consumption drivers is crucial for poverty alleviation and biodiversity conservation strategies. Bushmeat hunting and consumption in post-frontier Amazonia relies on relatively common species. Hunting was mostly driven by forest cover, whereas social relations determined consumption levels. Increasing wealth is unlikely to lead to changes in bushmeat hunting and consumption. Identifying how bushmeat is acquired is key to understanding the drivers of bushmeat hunting and consumption.